Computer-aided modeling of structure stabilizing disulfide bonds in recombinant human interferon-γ - Günther, Gero; Fechteler, Till; Villmann, Carmen; Zakaria, Hayssam; Schomburg, Dietmar; Otto, Bernd (Pharmaceutica acta Helvetiae, 1996)
We present a general search algorithm for possible insertion sites of disulfide bonds in proteins based on the coordinates of the solved X-ray or NMR structure, allowing the insertion of disulfide bonds with a minimum of conformational tension and backbone rearrangements. The fortran 77 program ‘Ssuitable’ was written for this purpose. This methodological approach was applied to recombinant human interferon-γ (rhu-IFN-γ), a cytokine of great pharmaceutical interest with a wide variety of biological activities including antiviral, antiproliferative and immunomodulatory effects. A model based on the CMα-coordinates obtained from the Brookhaven data base was built. Four different insertion sites were selected in the model, connecting the two subunits of the homodimer. The thermodynamic stability of rhu-IFN-γ is low, limiting its clinical application. We expect that the insertion of additional new disulfide bonds will enhance the thermodynamic stability as well as protect the protein against proteolytic degradation.